HYPERTENSION AND CARDIOVASCULAR RISK FACTORS IN CROATIA. DATA FROM THE 2017. WORLD HYPERTENSION DAY. (June 2018) - Milicic, B.; Dapic, K.; Domislovic, V.; Brozovic, M.; Drenjancevic, I.; Dobrincic, Z.; Gulin, M.; Cavrak, V. Herceg; Josipovic, J.; Jelakovic, A.; Kolar, L.; Leko, N.; et al.
Abstract : Objective: The aim of this study was to obtain data on prevalence and awareness of hypertension, cardiovascular risk factors, and life-style habits in individuals (aged 18 years or older) participating in the 2017 World Hypertension Day in Croatia. Design and method: Blood pressure (BP) was measured at 26 sites in 5 cities in Croatia. Along with BP measurement, a short questionnaire on hypertension awareness/salt intake/smartphone use was completed in the time of the interview. The average of two BP measurements, taken in seated position after a few minutes rest by a validated oscillometric device (Omron M6) was recorded. BP measurements were performed from 10 AM to 2 PM in hospital open points, central squares and pharmacies. BP was measured by physicians, trained nurses, pharmacist or medical students. This action was organized and supported by the Croatian Society of Hypertension. Results: A total of 2175 subjects, 873 (40.1%) men, 1211 (59.9%) women were examined. Men were older, had higher BP, BMI and waist circumference (64.7 (13.9)vs.61.8 (14.5);142.9/85.4 (19.8/11.7)vs.136.3/82.9 (21.2/11.3); 28.3 (4.4)vs.26.7 (5.4);103 (12.2)vs.92.8 (15.7), respectively). Proportion of patients with BMI over 25 and 25–30 kg/m2 was 32.4% and 20% respectively. In the whole group there were 53.4% subjects with BP 140/90 mmHg or higher (women vs.men 54.1% vs.45.9%, p < 0.001), 68.4% were aware of hypertension (men vs. women 66.9% vs.67.8%, p > 0.05). Positive family history (FH) for hypertension, stroke and myocardial infarction was found in 46.7%, 17.9% and 23.5% subjects respectively. FH was more frequently positive in women than in men (51.0% vs.40.3%, p < 0.001;20.3% vs.14.3%, p = 0.008, 26% vs.19.6%, p = 0.01). We failed to find association between BP values and positive FH. There were 18.7% smokers (more women never smoked 66.5% vs.57.1%, p < 0.001), average pack-years was 5. Only 9.4% of population declared regular physical activity (more than twice per week), and 49.7% were never physically active (no gender differences). Conclusions: Prevalence of subjects with BP values in hypertensive ranges is high, awareness is insufficient, and high proportion of subjects is obese and physically inactive. There is an urgent need of education not only hypertensives but general population as a true measure of primordial prevention.